2011
DOI: 10.1523/jneurosci.4640-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Hippocampus and Goal-Directed Spatial Decision Making

Abstract: Planning spatial paths through our environment is an important part of everyday life and is supported by a neural system including the hippocampus and prefrontal cortex. Here we investigated the precise functional roles of the components of this system in humans by using fMRI as participants performed a simple goal-directed route-planning task. Participants had to choose the shorter of two routes to a goal in a visual scene that might contain a barrier blocking the most direct route, requiring a detour, or mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 84 publications
11
128
1
1
Order By: Relevance
“…In rodents, ventral, but not dorsal, hippocampal stimulation increases locomotion [117][118] by engaging the NAc and mesolimbic dopamine (DA) system [119][120][121] , whereas inhibiting VH decreases locomotion 104 . This relationship with the NAc is also relevant to the observation that reward-or goal-directed functions localise to ventral parts of rodent hippocampus [122][123] and to the anterior human hippocampus 124 , given that the ventral striatum -in particular the NAc -is considered the 'limbic-motor interface' at which motivation-and emotion-related processing gains access to the motor system [125][126] . The rodent studies discussed above [117][118][119][120][121] examined dorsal vs. ventral functional dissociations, but the anatomical connectivity between the hippocampus and NAc in fact shows a graded topography 39 .…”
Section: Action and Motivationmentioning
confidence: 95%
“…In rodents, ventral, but not dorsal, hippocampal stimulation increases locomotion [117][118] by engaging the NAc and mesolimbic dopamine (DA) system [119][120][121] , whereas inhibiting VH decreases locomotion 104 . This relationship with the NAc is also relevant to the observation that reward-or goal-directed functions localise to ventral parts of rodent hippocampus [122][123] and to the anterior human hippocampus 124 , given that the ventral striatum -in particular the NAc -is considered the 'limbic-motor interface' at which motivation-and emotion-related processing gains access to the motor system [125][126] . The rodent studies discussed above [117][118][119][120][121] examined dorsal vs. ventral functional dissociations, but the anatomical connectivity between the hippocampus and NAc in fact shows a graded topography 39 .…”
Section: Action and Motivationmentioning
confidence: 95%
“…5 In addition to parietal lobe, hippocampus also has a role in spatial ability. 12 Other previous study found that hippocampus had greater activity in spatial ability. 12 It can be seen using functional Magnetic Resonance Imaging (fMRI).…”
Section: -11mentioning
confidence: 91%
“…12 Other previous study found that hippocampus had greater activity in spatial ability. 12 It can be seen using functional Magnetic Resonance Imaging (fMRI). 12 Uniquely, hippocampusis is more connected with parietal lobe on male, and temporal lobe on female.…”
Section: -11mentioning
confidence: 91%
See 1 more Smart Citation
“…The principal motivation to examine their topography arises from the growing evidence for functional differences along the anterior–posterior axis of the hippocampus (Collin, Milivojevic, & Doeller, 2015; Fanselow & Dong, 2010; Poppenk, Evensmoen, Moscovitch, & Nadel, 2013; Strange, Witter, Lein, & Moser, 2014). For instance, evidence from functional neuroimaging studies suggests a role of the posterior hippocampus in spatial navigation (e.g., Hartley, Maguire, Spiers, & Burgess, 2003), whereas anterior hippocampus has been associated with goal‐directed spatial decision making (Viard, Doeller, Hartley, Bird, & Burgess, 2011). Thus, a method that would allow the anatomical dissociation of fibers associated with anterior and posterior hippocampal regions in humans would aid the study of functional dissociation between these different hippocampal networks.…”
Section: Introductionmentioning
confidence: 99%